Strategies for Managing Student Services to Optimise Service Delivery Based on the Student Information System - Ilfi Nur Diana; Moh. Padil; Aidatul Karimah (Kopertais Wilayah III Yogyakarta, 2026)
This study examines the strategic management of student services to optimise service delivery based on the Student Information System (SIS) at the Al-Yasini Integrated Islamic Boarding School. The increasingly complex development of Islamic boarding schools demands an integrated, effective, and technology-based service system. However, the implementation of the SIS still faces various challenges, including human resources, system integration, and managerial oversight. This study aims to: (1) identify the forms and characteristics of SIS-based services for boarding school students; (2) analyse the obstacles to their implementation; and (3) analyse management strategies for optimising SIS-based services. The method used is a qualitative approach employing a case study design. Data collection techniques included observation, interviews, and documentation, with data analysis involving data reduction, data presentation, conclusion, and triangulation. The research findings indicate that SIS-based services encompass administrative services, attendance tracking, authorisation processes, communication with students’ guardians, and digital data management, all characterised by speed, accuracy, and transparency. The main constraints include limited staff competence in technology, a lack of system integration, and the continued use of manual systems. The strategies implemented include applying management functions (planning, organising, executing, and monitoring), strengthening institutional policies, enhancing staff competencies through training, and developing a more integrated system. These strategies have been shown to improve the efficiency, effectiveness, and accountability of services for students. Keywords: Strategic Management; Student Services; Student Information System; Service Optimisation